2019
DOI: 10.1111/fwb.13325
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent competition between juvenile salmonids in small streams

Abstract: Biotic interactions affect species distributions, and environmental factors that influence these interactions can play a key role when range shifts in response to environmental change are modelled. In a field experiment using enclosures, we studied the effects of the thermal habitat on intra‐ versus inter‐specific competition of juvenile Dolly Varden Salvelinus malma and white‐spotted charr Salvelinus leucomaenis, as measured by differences in specific growth rates during summer in allopatric and sympatric tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…a juvenile bottleneck). Myrvold and Kennedy (2015) showed empirically that warming increases intraspecific competition and causes juvenile bottlenecks in their study of wild steelhead, and Watz et al (2019) found support for temperature effects on growth via interspecific competition in two species of charr. However, to our knowledge, no studies have until now linked juvenile bottlenecks to temperature-dependent predation and interspecific competition, and the resulting effects of warming on the composition of intraguild predation communities.…”
Section: Discussionmentioning
confidence: 96%
“…a juvenile bottleneck). Myrvold and Kennedy (2015) showed empirically that warming increases intraspecific competition and causes juvenile bottlenecks in their study of wild steelhead, and Watz et al (2019) found support for temperature effects on growth via interspecific competition in two species of charr. However, to our knowledge, no studies have until now linked juvenile bottlenecks to temperature-dependent predation and interspecific competition, and the resulting effects of warming on the composition of intraguild predation communities.…”
Section: Discussionmentioning
confidence: 96%
“…Responses to temperature and salinity are likely to define components of performance that are relevant for, for example, competition and larval transport. For instance, competitive abilities can change according to the temperature where such competition occurs (Tomanek & Helmuth, 2002;Watz et al, 2019); comparative studies should provide insights into how the outcome of competition is modulated by responses to combination of temperature and salinity. In addition, larval transport in many crustaceans depends on circatidal or diel migration behavior, which should be driven by the capacity of larvae to accumulate and use energy for vertical swimming.…”
Section: Perspectives For Model Developmentmentioning
confidence: 99%
“…As such, the stronger avoidance response of the smaller 0+ brown trout could indicate that they were more susceptible to predation than the larger 0+ brook trout due to gape limitations of the 1+ individuals (Keeley & Grant, 2001). With the multitude of cues present in a stream, it is unlikely that there is only one factor that determines the spatial distribution of individuals, rather it may be a combination of visual and chemical cues (Brown, 2003;Höjesjö et al, 2015), presence of predators (Ferrari et al, 2010) and habitat variability (Höjesjö et al, 2004;Watz et al, 2019) that helps form hierarchies and spatial distribution of individuals (Kaspersson & Höjesjö, 2009;Nakano, 1995). The results from the territorial contest after manipulating residence duration was rather surprising as only one brown trout won the territorial contest.…”
Section: Discussionmentioning
confidence: 99%